Pengaruh tingkat kepuasan pelayanan, pemahaman perpajakan, keadilan perpajakan, sanksi perpajakan dan kesadaran perpajakan terhadap tingkat kepatuhan wajib pajak orang pribadi pada kpp pratama senapelan Pekanbaru - Akromi Khairina Asbar; Ruhul Fitrios; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research was investigated the satisfaction services,understanding, justice, tax penalties and tax awareness to individual taxpayers. This study is a replication of Hanna (2008) study. It also intended to test the results of the previous study in different contextThis research use samples of Individual taxpayer underpayment in Pelayanan Pajak Kota Office Pekanbaru City Senapelan. This research use 100 samples of Individual taxpayer underpayment in Pelayanan Pajak Kota Office on Pekanbaru City Senapelan selected using purposive sampling method. The criteria of purposive sampling method individual taxpayers registered in Pekanbaru City Tax Office with the characteristics listed underpayment during year period 2009 until 2012. The statistical method uses in this research are multiple regressions by means of SPSS version 17.0The results indicate that satisfaction services, understanding, justice, taxpenalties have positive influence and significance to individual taxpayers. While tax awareness have positive influence and does not significance to individual taxpayers.Keywords : satisfaction services, understanding, justice, tax penalties, tax awareness, individual taxpayers